The Kinetic Model of Calcination and Carbonation of Anadara Granosa - Rashidi, Nor Adilla (2012)
Utilization of calcium-based adsorbent in carbon dioxide (CO2) separation from the gas stream through the calcination and carbonation process is extensively applied in the gas purification process, especially at the elevated reaction temperature. Typically, natural calcium carbonates (CaCO3) such as the limestone, magnesite and dolomite are widely consumed in the process due to their low cost and large abundance of these materials. However, in this research study, the potential of waste cockle shell as the CaCO3 sources were investigated. The main objectives of the work are to examine the influence of the process variables such as heating rate, particle size, temperature and residence time on the calcination rate. Therefore, Arrhenius equation was used to explain the process reactivity. The calcination process were carried out for various particles sizes (<0.125-4.00 mm), calcination temperatures (750-950oC), heating rate (10-50oC/min) and also the calcination duration time (30-60 min). Using zero order reaction, the activation energy (Ea) and also the pre-exponential factor (A) were determined. In addition, the effect of temperature (500-850oC) on carbonation reaction was also studied. Based on the kinetic analysis, it proves that the resistivity towards the diffusion process is significant in carbonation as compared to chemical reaction at the surface.